2012
DOI: 10.1002/oa.2294
|View full text |Cite
|
Sign up to set email alerts
|

Entheseal Changes: Do They Reflect Socioeconomic Status in the Early Medieval Central European Population? (Mikulčice – Klášteřisko, Great Moravian Empire, 9th – 10th century)

Abstract: Entheseal changes (EC) of skeletons are supposed to reflect the physical activity of our ancestors. Similarly, the elements of the burial rite (e.g. grave goods, burial depth) are presumed to be related to the social status of individuals. The aim of this study was to verify the existence of relationships between EC distribution and archaeological descriptors providing information on social status. Fibrocartilaginous entheses of upper and lower limb bones of 115 individuals (aged 20–50 years) from the early me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Muscle attachment sites (entheses) are used by researchers in fields as diverse as bioarchaeology and palaeontology to infer cultural behaviour (Weiss, 2007; Molnar, 2010), technology use (Eshed et al, 2004; Marzke et al, 2007; Drapeau, 2008), subsistence strategies (Hawkey, 1998), labour differences (Churchill and Morris, 1998; Villotte et al, 2010; Weiss, 2010; Havelková et al, 2011; Niinimäki, 2011; Niinimäki and Sotos, 2013), social stratification (Molnar, 2006; Havelková et al, 2011, 2013; Henderson et al, 2013; Nolte and Wilczak, 2013), locomotor patterns (Davis, 1964; McGowan, 1979; Eliot and Jungers, 2000; Wang et al, 2004; Zumwalt, 2005, 2006), and evolutionary pathways (Davis, 1964; McGowan, 1979; Eliot and Jungers, 2000; Wang et al, 2004; Marzke and Shrewsbury, 2006; Drapeau, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Muscle attachment sites (entheses) are used by researchers in fields as diverse as bioarchaeology and palaeontology to infer cultural behaviour (Weiss, 2007; Molnar, 2010), technology use (Eshed et al, 2004; Marzke et al, 2007; Drapeau, 2008), subsistence strategies (Hawkey, 1998), labour differences (Churchill and Morris, 1998; Villotte et al, 2010; Weiss, 2010; Havelková et al, 2011; Niinimäki, 2011; Niinimäki and Sotos, 2013), social stratification (Molnar, 2006; Havelková et al, 2011, 2013; Henderson et al, 2013; Nolte and Wilczak, 2013), locomotor patterns (Davis, 1964; McGowan, 1979; Eliot and Jungers, 2000; Wang et al, 2004; Zumwalt, 2005, 2006), and evolutionary pathways (Davis, 1964; McGowan, 1979; Eliot and Jungers, 2000; Wang et al, 2004; Marzke and Shrewsbury, 2006; Drapeau, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Archaeological excavations in the Mikulčice settlement agglomeration have uncovered over 2500 burials mostly associated with church cemeteries (Poláček, 2008). Previous bioarchaeological analyses of Mikulčice skeletal remains have revealed aspects of lifestyle of the Great Moravian populations, including sex-and/or status-based differences in health, physical activity, and diet (Bigoni et al, 2013;Garcin et al, 2010;Havelková et al, 2011Havelková et al, , 2013Velemínský et al, 2009). Analyses of dental and skeletal indicators of health have provided evidence for poorer health in rural compared to urban (castle and subcastle) inhabitants, with higher incidences of cribra orbitalia and linear enamel hypoplasias in the former (Garcin et al, 2010;Velemínský et al, 2009).…”
Section: Great Moraviamentioning
confidence: 96%
“…A comparison between castle and hinterland sites within the Mikulčice agglomeration revealed that males from the agricultural hinterland have the highest prevalence of enthesopathies, presumably due to activities associated with farming, such as tilling and harvesting of crops using sickles (Havelková et al, 2011). At the sub-castle site of Mikulčice-Klášteřisko, the location of entheseal changes was found to be associated with archaeological indicators of social status (burial features and type of grave goods (Havelková et al, 2013)). Status-based dietary differences have also been proposed based on a higher degree of cranial directional asymmetry in individuals buried in the sub-castle versus castle area at Mikulčice (Bigoni et al, 2013).…”
Section: Great Moraviamentioning
confidence: 97%
“…It is widely accepted that EC reflect the effect of muscle usage throughout the course of life. However, factors such as the age (Milella et al, 2012;Henderson, 2013;Niinimäki and Baiges Sotos, 2013;Takigawa, 2014;Schrader, 2015), sexual differences due to the existing gender-based differences between endocrine and metabolic systems (Havelková et al, 2013) alongside the particular anatomy of the attachment site have been claimed to be related to the level of the EC expression (Villotte et al, 2010b;Milella et al, 2012). From a medical point of view, EC can be induced by numerous conditions, ranging from pathological to behavioural (Jurmain, 2009).…”
Section: Entheseal Changes (Ec)mentioning
confidence: 99%
“…Notwithstanding the questions concerning the possibility of establishing a relation between EC and activity, some recent studies of EC of skeletons are based on the hypothesis that the EC reflect the physical activity of our forebears (Lieverse et al, 2009;Havelková et al, 2013;Henderson, 2013;Lieverse et al, 2013;Villotte and Knüsel, 2014;Schrader, 2015). This is due to the fact that specific movements carried out frequently affect both the structure and morphology of entheses (Benjamin and Hillen, 2003;Galtés et al, 2006).…”
Section: Recording Of Entheseal Change Datamentioning
confidence: 99%